The relationships between types of motivation and second language acquisitions among science students - Zakaria, Zakhwan Aunie Al- Haffizz; Hashim, Jamalludin Helmi (2018)
Several researchers (for example, Tsutsui and Fujiwara, 2015; Golten, Genc, 2016) noted that there is a relationship between the positive attitude and motivation with the creativity in the learning process which lead to the cultivating the independent learning.The present paper will report the first part out of two of the study; i.e., the influence of extrinsic and intrinsic motivation in learning English as Second Language (ESL).The objectives of the present study are twofolds: (i) to determine the type of motivations (either extrinsic or intrinsic) and (ii) to identify the relationship between those motivation and Second Language acquisition among science students.Using a Purposive Sampling method, 70 returned (out of 80) questionnaires were analyzed from one of the Private Higher Education Institution in Malaysia.The results showed that the respondents are intrinsically motivated to learn ESL and the Cohen d” statistic (p< 0.05) which means that there is a high relationship between intrinsic motivation with the ESL acquisition ability.As for future research, bigger samples size (in term of the number of respondents as well as the areas of studies) should be used in order to ensure the results are applicable and can be generalize to a larger population.